New immigrant : on the first locally produced film in Singapore and Malaya - Hee, Wai Siam (2014)
Based on historical evidence from a large number of newspapers from the 1920s, this article disputes the assertion of the international academic circle that the film Xin Ke (New Immigrant) was never released. The article demonstrates the historical significance of Xin Ke and establishes its status as the first Singaporean-Malayan film. The article also makes several important contributions to our understanding of Xin Ke and its creators. First, it describes the origins of, and public response to, the Nanyang Liu Bei-jin Film Company. Second, it examines the moving and tragic life of Liu Bei-jin, the former Namchow mechanic who became the film company's head and who later left Singapore and Malaya to fight in the Chinese War of Resistance against Japan. Third, it describes the Xin Ke production team and the film's reception. It investigates the problems that the film confronted at the time of its production, including censorship imposed by the British colonial government during the 1920s. Fourth, it discusses the oscillation found in Xin Ke's screenplay between the Nanyang and Chinese styles of literature and art. Finally, it examines the manner in which the film addressed the disputes between the two major Chinese communities in Nanyang, namely the ‘Xin Ke’ (new immigrants) and the Peranakan (Straits Chinese).